Hyperbranched Polyglycerol-Coated Magnetic Nanoparticles as Draw Solute in Forward Osmosis - Yang, Hee-Man; Seo, Bum-Kyoung; Lee, Kune-Woo; Moon, Jei-Kwon (Asian Journal of Chemistry, 2014)
Water soluble hyperbranched polyglycerol-coated magnetic nanoparticles (HPG-MNPs) were introduced as a new draw solute in forward osmosis (FO) to prevent their aggregate for better forward osmosis performance. The HPG-MNPs were successfully synthesized by grafting polyglycerol onto the surfaces of magnetite through a ring-opening polymerization of glycidol. The HPG-MNPs exhibit excellent dispersibility in aqueous solution and the highest water flux achieved in a forward osmosis process was 6.7 L/m2h for HPG-MNPs when deionized water is used as the feed solution.